Feeding of premature infants at the outpatient stage - V. A. Skvortsova; E. L. Pinaeva-Slysh; I. A. Belokrylov (Лечащий Врач)
Background. The article highlights the key points of the report on the feeding of premature infants at the outpatient stage, presented by the chief researcher of the Laboratory of Nutrition of healthy and sick children of the National Medical Research Center for Children's Health of the Ministry of Health of the Russian Federation, Professor of the Department of Neonatology Moscow Regional Research Clinical Institute named after M. F. Vladimirsky, Doctor of Medical Sciences Vera Alekseevna Skvortsova together with Evgeniia L. Pinaeva-Slysh at the Scientific and Practical Conference ″Interdisciplinary aspects of Women's and Children's health″, which took place on September 29 as part of the XXIV All-Russian Scientific and Educational Forum ″Mother and Child″.Objective. To consider the possibilities of feeding deeply premature babies with very low and extremely low birth weight at the outpatient stage, presenting the most optimal options, which include the long-term use of breast milk fortifiers during breastfeeding, and with artificial – the use of a specialized mixture for premature babies up to 52 weeks of postconceptual age as well as the introduction of complementary foods in order to correct nutritional deficiencies.Conclusion. Thanks to a specialized formula developed by a domestic manufacturer in collaboration with leading neonatologists of the country for feeding deeply premature infants, which can be used not only in the hospital, but also after discharge, it has become possible to improve the indicators of physical and cognitive development of such children and influence the dynamics of the catching-up growth process.